Ecotoxicity characterization of chemicals: Global recommendations and implementation in USEtox. (January 2023) - Owsianiak, Mikołaj; Hauschild, Michael Z.; Posthuma, Leo; Saouter, Erwan; Vijver, Martina G.; Backhaus, Thomas; Douziech, Mélanie; Schlekat, Tamar; Fantke, Peter
Abstract: Chemicals emitted to the environment affect ecosystem health from local to global scale, and reducing chemical impacts has become an important element of European and global sustainability efforts. The present work advances ecotoxicity characterization of chemicals in life cycle impact assessment by proposing recommendations resulting from international expert workshops and work conducted under the umbrella of the UNEP-SETAC Life Cycle Initiative in the GLAM project (Global guidance on environmental life cycle impact assessment indicators). We include specific recommendations for broadening the assessment scope through proposing to introduce additional environmental compartments beyond freshwater and related ecotoxicity indicators, as well as for adapting the ecotoxicity effect modelling approach to better reflect environmentally relevant exposure levels and including to a larger extent chronic test data. As result, we (1) propose a consistent mathematical framework for calculating freshwater ecotoxicity characterization factors and their underlying fate, exposure and effect parameters; (2) implement the framework into the USEtox scientific consensus model; (3) calculate characterization factors for chemicals reported in an inventory of a life cycle assessment case study on rice production and consumption; and (4) investigate the influence of effect data selection criteria on resulting indicator scores. Our results highlight the need for careful interpretation of life cycle assessment impact scores in light of robustness of underlying species sensitivity distributions. Next steps are to apply the recommended characterization framework in additional case studies, and to adapt it to soil, sediment and the marine environment. Our framework is applicable for evaluating chemicals in life cycle assessment, chemical and environmental footprinting, chemical substitution, risk screening, chemical prioritization, and comparison with environmental sustainability targets. Graphical abstract: Image 1 Highlights: Global recommendation for ecotoxicity characterization of chemicals. Matching mathematical framework for calculating effect and exposure factors. New characterization factors derived for a set of chemicals from a case study. Advancing current approaches for life cycle impact assessment of chemicals.